Communication and Ethics of Modern Indonesian Business in The Perspective of Islamic Economy Law - Saleh, Sadhriany Pertiwi; Cangara, Hafied; Sudirman, Indrianti; Unde, Alimuddin; Putra, Fajar Dwi (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
As one of the countries with the largest Muslim population in the world, Indonesia exhibits a universal modern business environment where Islamic values are not only religious principles, but also serve as a legal framework and social norms. This research seeks to uncover complex legal and moral dilemmas in business communication in Indonesia. This article uses qualitative methods with a communication approach and Islamic economic law. Data was collected by means of literature study or document analysis. This research found how important the relationship between Islamic ethical rules and applicable legal regulations and religious characteristics is in modern communication in the business world in Muslim-majority countries. Therefore, adopting Islamic ethics in the current business communication process in Indonesia is something that is very urgent. Through ethical and legal stakeholder resolutions, businesses will improve their reputation and build trust with stakeholders, and facilitate sustainable economic development in the country. In the context of Islamic economic law, collaboration between ulama and legal experts is very important for companies in Indonesia as a way to ensure compliance with ethics, increase CSR efforts, conduct sharia compliance audits, and fully engage with stakeholders. This study finds the value of collaboration as an instrument of business sustainability, ethical behavior, and engagement with stakeholders.